Патоморфологические изменения периферической нервной системы при рассеянном склерозе = Pathological changes of peripheral nervous system in multiple sclerosis - E. V. Markovskaya; A. S. Shapkin (Kazimierz Wielki University, 2016)
Markovskaya E. V., Shapkin A. S. Патоморфологические изменения периферической нервной системы при рассеянном склерозе = Pathological changes of peripheral nervous system in multiple sclerosis. Journal of Education, Health and Sport. 2016;6(8):267-283. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.60514 http://ojs.ukw.edu.pl/index.php/johs/article/view/3758       The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 01.08.2016. Revised 08.08.2016. Accepted: 19.08.2016.     Патоморфологические изменения периферической нервной системы при рассеянном склерозе   Е. В. Марковская, А. С. Шапкин   Харьковский национальный медицинский университет   Резюме Проведено исследование патоморфологических изменений периферической нервной системы и сосудов кожи у больных рассеянным склерозом. Отмечено, что в элементах периферической нервной системы при рассеянном склерозе возникают демиелинизация и дистрофические изменения нервных волокон в виде разволокнения, склероза, варикозного вздутия и очагового уменьшения шванновских клеток. В периневральном и периваскулярном пространстве кожи выявляются воспалительные изменения, при этом в клетках лимфоцитарного воспалительного инфильтрата экспрессируется большое количество циклооксигеназы-2 и индуцибельной фракции синтазы оксида азота. Одним из звеньев патогенеза, усиливающих демиелинизацию и дистрофические изменения нервных волокон, может служить активация в шванновских клетках индуцибельной фракции синтазы оксида азота и циклооксигенезы-2. Наличие эндотелиальной дисфункции и воспалительных изменений в компонентах периферической нервной системы при разных типах течения рассеянного склероза, в том числе и в стадии ремиссии, следует учитывать при назначении патогенетической терапии. Ключевые слова: рассеянный склероз, морфология, эндотелиальная дисфункция.       Pathological changes of peripheral nervous system in multiple sclerosis   E. V. Markovskaya, A. S. Shapkin   Kharkiv National Medical University   Abstract Scientific research of pathomorphological changes of peripheral nervous system and skin vessels in patients with multiple sclerosis was done. It was marked that demyelination and dystrophic changes in nerves in form of stratification, varicose distension, sclerosis and local decreasing of Schawann cells are detected. Inflammatory changes in perineural and perivascular space of the skin were revealed, increased level of cyclooxygenase-2 and inducible nitric oxide synthase in lymphocytic inflammatory infiltration are expressed. One of pathogenetic mechanism leading to demyelination could be activation of inducible nitric oxide synthase and cyclooxygenase-2 inSchwann cells. So, endothelial dysfunction and inflammatory changes in elements of peripheral nervous system in different types of courses of multiple sclerosis, also in remission, should be taking into consideration for prescribing pathogenetic treatment.   Key words: multiple sclerosis, morphology, endothelial dysfunction.   ПАТОМОРФОЛОГІЧНІ ЗМІНИ ПЕРИФЕРИЧНОЇ НЕРВОВОЇ СИСТЕМИ ПРИ РОЗСІЯНОМУ СКЛЕРОЗІ   О. В. Марковська, А. С. Шапкін   Харківський національний медичний університет   Резюме Проведено дослідження патоморфологічних змін периферичної нервової системи і судин шкіри у хворих на розсіяний склероз. Відзначено, що в елементах периферичної нервової системи при розсіяному склерозі виникають демієлінізация та дистрофічні зміни нервових волокон у вигляді розволокнення, склерозу, варикозного здуття і осередкового зменшення шванновських клітин. У периневральному і периваскулярному просторах шкіри виявляються запальні зміни, при цьому в клітинах лімфоцитарного запального інфільтрату експресується велика кількість циклооксигенази-2 і синтази індуцибельної фракції оксиду азоту. Одною з ланок патогенезу, що підсилюють демієлінізацію і дистрофічні зміни нервових волокон, може служити активація в шванновських клітинах, індуцибельної фракції синтази оксиду азоту та циклооксигенеза-2. Наявність ендотеліальної дисфункції і запальних змін в компонентах периферичної нервової системи при різних типах перебігу РС, в тому числі і в стадії ремісії, слід враховувати при призначенні патогенетичної терапії.   Ключові слова: розсіяний склероз, морфологія, ендотеліальна дисфункція.